Circadian clocks govern calorie restriction—mediated life span extension through BMAL1‐ and IGF‐1‐dependent mechanisms. Issue 4 (23rd December 2015) - Patel, Sonal A.; Chaudhari, Amol; Gupta, Richa; Velingkaar, Nikkhil; Kondratov, Roman V.
Abstract : Calorie restriction (CR) increases longevity in many species by unknown mechanisms. The circadian clock was proposed as a potential mediator of CR. Deficiency of the core component of the circadian clock—transcriptional factor BMAL1 (brain and muscle ARNT [aryl hydrocarbon receptor nuclear translocator]‐like protein 1)—results in accelerated aging. Here we investigated the role of BMAL1 in mechanisms of CR. The 30% CR diet increased the life span of wild‐type (WT) mice by 20% compared to mice on an ad libitum (AL) diet but failed to increase life span of Bmal1 –/– mice. BMAL1 deficiency impaired CR‐mediated changes in the plasma levels of IGF‐1 and insulin. We detected a statistically significantly reduction of IGF‐1 in CR vs. AL by 50 to 70% in WT mice at several daily time points tested, while in Bmal1 –/– the reduction was not significant Insulin levels in WT were reduced by 5 to 9%, while Bmal1 –/– induced it by 10 to 35% at all time points tested. CR up‐regulated the daily average expression of Bmal1 (by 150%) and its downstream target genes Periods (by 470% for Per1 and by 130% for Per2 ). We propose that BMAL1 is an important mediator of CR, and activation of BMAL1 might link CR mechanisms with biologic clocks.—Patel, S. A., Chaudhari, A., Gupta, R., Velingkaar, N., Kondratov, R. V. Circadian clocks govern calorie restriction‐mediated life span extension through BMAL1‐ and IGF‐1‐dependent mechanisms. FASEB J. 30, 1634–1642 (2016). www.fasebj.org